The Implementation of Islamic Religious Education Learning in Developing Students’ Religious Character - Syntia, Tiara Angel; Utami, Eca Putri; Sulastri, Selvi Dwi; Mustamin, Abdul Aziz bin; Septiria, Dalima (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study examines the implementation of Islamic Religious Education learning in developing students’ religious character at SD Negeri 35 Kota Bengkulu. The research employed a qualitative descriptive approach to explore classroom practices, teacher roles, and supporting conditions influencing character development. Data were collected through classroom observations, semi-structured interviews, and documentation analysis involving teachers, students, and the school principal. The findings indicate that Islamic Religious Education learning is implemented through structured instructional processes, varied teaching methods, contextual learning materials, and consistent classroom management. Teachers’ exemplary behavior and interactive learning strategies play a significant role in reinforcing religious values. Supportive school culture and parental collaboration strengthen students’ religious character, while challenges such as limited instructional time, student diversity, and external influences require adaptive strategies. The study underscores the importance of coherent implementation and professional commitment in optimizing Islamic Religious Education at the elementary school level.